The changing epidemiology of community‐acquired pneumonia: nationwide register‐based study in Sweden. (13th August 2019) - Naucler, P.; Henriques‐Normark, B.; Hedlund, J.; Galanis, I.; Granath, F.; Örtqvist, Å.
Abstract: Background: There is limited evidence on the impact of pneumococcal conjugate vaccine childhood immunization programmes (PCV‐CIP) on community‐acquired pneumonia (CAP) in individuals with underlying diseases. Methods: A nationwide cohort study using Swedish health registers to assess the incidence of hospitalization with all‐cause (AC‐CAP) and pneumococcal or lobar (PL‐CAP) CAP between 2005 and 2015, in relation to PCV‐CIP introduction in 2007–09. Results: In total, 303 691 episodes of AC‐CAP occurred, of which 14 225 were PL‐CAP. Comparing before (2005–06) with after (2014–15) PCV‐CIP, relative incidence reductions were 36% (95% Confidence Interval 32–40), 20% (14–25) and 16% (11–22) of AC‐CAP for age groups < 2, 2–4 and 5–17 years, respectively, with similar reductions in young children with and without comorbidities. The reductions were more pronounced for PL‐CAP. In the age groups 40–64, 65–74, 75–84 and ≥85 years there were relative increases of 11% (8–14), 18% (15–22), 15% (12–17) and 30% (27–34) of AC‐CAP, respectively, but these increases were attenuated after adjustment for admittance practices using four control conditions. In adults with comorbidities, there was an increase in incidence of AC‐CAP, and PL‐CAP, in contrast to adults without reported underlying diseases where the incidence was stable or diminished for some age groups. Over the study period, there was an increased proportion of pneumonia patients with underlying diseases in all ages. Conclusion: This emphasizes that direct preventive interventions should be targeted towards individuals with underlying diseases. Future studies should investigate reasons for the observed increased risk in adults with comorbidities, for example due to pneumococcal nonvaccine serotypes, or other pathogens, preferentially affecting subjects with underlying diseases. Abstract :